Hospital Service Climate: Gender Analysis in Nursing Staff - Trirahardjo, Sunggoro; Kadiyono, Anissa Lestari; Jannah, Azalea Raudhatul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The hospital’s responsibility to provide excellent service to patients reflects the expectations of the government, society, and hospital management. Efforts to achieve this can be realized by establishing a strong Service Climate within the organization. Service Climate refers to employees’ perceptions of the procedures, actions, and behaviors expected by the organization in relation to customer service and represents an essential factor in improving service performance. This study aims to examine the role of gender in shaping perceptions of service climate in hospitals, referring to the theory of Schneider and White (2004). The research hypothesis stated that there is a difference in perceptions of service climate between male and female nurses. This study employed a quantitative descriptive design with a convenience random sampling technique. The participants consisted of 254 nurses who handled stunting cases in several hospitals across West Java. The service climate instrument comprised 22 items and demonstrated high internal consistency (Cronbach’s Alpha = 0.968). Descriptive results showed a mean score of 70,05 (SD = 8.56), indicating that the overall perception of service climate was in the moderately high category. The independent samples t-test revealed a significant difference between female nurses (M = 70.92, SD = 8.99) and male nurses (M = 68.04, SD = 7.12), t(252) = 2.493, p = 0.013, with a small-to-moderate effect size (Cohen’s d = 0.34). Further dimensional analysis found significant differences in four out of five dimensions. These findings confirm that gender plays a role in shaping perceptions of hospital service climate, although it is not the sole determining factor.Tugas Rumah Sakit dalam memberikan pelayanan yang prima pada pasien merupakan harapan dari pemerintah, masyarakat, maupun manajemen Rumah Sakit itu sendiri. Upaya untuk mewujudkannya dapat dilakukan dengan membentuk Iklim Pelayanan di lingkungan kerja. Iklim Pelayanan merupakan persepsi karyawan terhadap prosedur, tindakan, dan perilaku yang diharapkan organisasi terkait dengan pelayanan kepada pelanggan, serta menjadi faktor penting dalam peningkatan kinerja pelayanan. Penelitian ini bertujuan menguji peran gender dalam pembentukan persepsi terhadap service climate di rumah sakit dengan mengacu pada teori Schneider dan White (2004). Hipotesis penelitian menyatakan bahwa terdapat perbedaan persepsiservice climate antara perawat laki-laki dan perempuan. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan teknik pengambilan sampel convenience random sampling. Subjek penelitian berjumlah 254 perawat yang menangani kasus stunting di berbagai rumah sakit di Jawa Barat. Instrumen service climate terdiri dari 22 butir dengan reliabilitas sangat tinggi (Cronbach’s Alpha = 0,968). Hasil deskriptif menunjukkan skor rata-rata 70,05 (SD = 8,56) yang mengindikasikan persepsi terhadap iklim pelayanan berada pada kategori cukup tinggi. Hasil independent samples t-test menunjukkan perbedaan signifikan antara perawat perempuan (M = 70,92, SD = 8,99) dan laki-laki (M = 68,04, SD = 7,12), t(252) = 2,493, p = 0,013, dengan ukuran efek Cohen’s d = 0,34. Analisis dimensi menunjukkan perbedaan signifikan pada empat dari lima dimensi service climate. Temuan ini menegaskan bahwa gender berperan dalam pembentukan persepsi terhadap iklim pelayanan, meskipun bukan faktor tunggal yang menentukan.